The Lexicographic Treatment of Xitsonga Kinship Terminologies in Selected Bilingual Dictionaries - Respect Mlambo; Muzi Matfunjwa (African Journal of Inter-Multidisciplinary Studies)
Kinship terminologies, which vary across cultures and languages, present challenges for lexicographers in creating bilingual dictionaries. Effective bilingual dictionaries must accurately and comprehensively reflect kinship terms and their equivalents. This study explores the lexicographic treatment of Xitsonga kinship terms in bilingual dictionaries, focusing on their definition, translation, and cross-referencing in English-Xitsonga contexts. It addresses the lexicographic challenges posed by kinship terms' cultural specificity and structural diversity across languages. Using a descriptive qualitative methodology, data were collected from the English-Tsonga/Tsonga-English Pocket Dictionary (2008) and the Pharos Bilingual Dictionary: English-Xitsonga/Xitsonga-English (2021). This study is guided by the user-driven approach to lexicography. The study has found that even though bilingual dictionaries offer some accurate equivalents, they often lack full definitions and overlook specific cultural nuances. Cultural differences between English and Xitsonga were identified as key factors limiting the inclusion of kinship equivalents. To improve the accuracy and cultural representation of kinship terms, this study recommends expanding definitions to cover a wider range of familial relationships and ensuring all relevant Xitsonga equivalents are included to reflect its cultural distinctions. These findings contribute to understanding the challenges and opportunities of presenting kinship terms and informing the improvement of bilingual lexicographic resources for Xitsonga.